Fixed Point Results for Enriched Interpolative Type Multivalued Contractions via a Simulation Function (European Journal of Pure and Applied Mathematics, 2025)
In this paper, using a simulation function in the sense of Khojasteh, we define multivalued enriched interpolative Kannan-type and Hardy-Rogers-type contractions from a convex metric space U to the collection of closed and bounded subsets of U . We establish two fixed points for these types of multivalued contractions. Our results are illustrated by examples and followedby some corollaries. As a consequence of each main result, a theorem on data dependence of fixed point is proved.